Multi objective Adaptive Tumbling Bacterial Foraging in VAR Solutions for Sustainable Power System Operation - E. E. Hassan; T. K. A. Rahman; Z. Zakaria; N. Bahaman; M. H. Jifri (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
The application of the developed optimization technique Multi Objective Adaptive Tumbling Bacterial Foraging (MOATBFO) was introduced to solve the multi objective Reactive Power Planning (RPP) problems. The objective of conventional RPP problems is to minimize the total power losses in a system. However, in this study, the aspect of security was also taken into consideration in terms of voltage stability condition in solving RPP problems. Hence, the RPP problem is now termed as security constrained RPP (SCRPP) and generalized into a multi objective function via weighted sum method that labeled as MOSCRPP. The best minimum voltage solution for the network is aimed in ensuring the sustainable power system operation.  In order to verify the performance of the proposed technique were used for MOSCRPP in the IEEE 57 bus system thus the comprehensive analyses were also conducted with other multi objective Meta heuristic Evolutionary Programming (Meta-EP). From the results it shows that the multi objective ATBFO optimization is able to give better overall improvement in the objective functions for SCRPP problems.